The online teaching survival guide simple and practical pedagogical tips - Boettcher, Judith V.; Conrad, Rita-Marie (Jossey-Bass, 2021)
"Recently, schools across the globe have experience a shift to online courses and teaching. With more universities and colleges offering online courses, there is a great trend in faculty who traditionally teach face-to-face needing to learn how to teach online. The theories and techniques of online teaching, or of blended courses that incorporate technology to improve learning, are vastly different from traditional educational pedagogy. Faculty are facing a huge learning curve and need a theory-based, hands-on practical guide in order to get started. Even experienced faculty can benefit from a comprehensive guide grounded in solid theory to help them take their courses to the next level"--Provided by publisher.